2005
DOI: 10.1080/10242690500070045
|View full text |Cite
|
Sign up to set email alerts
|

Defence expenditures and external debt in Turkey

Abstract: The causal relationship between defence expenditures and external debt is investigated by applying a multivariate model. Our estimation results indicate that defence expenditures and external debt for Turkey are cointegrated. To test for Granger causality in the presence of cointegration between variables, we employ a vector error correction model. Empirical results for Turkey over the period 1955-2000 suggest a long run and short run unidirectional causality running from defence expenditures to external debt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 20 publications
1
7
0
2
Order By: Relevance
“…In another study for the same sample and country, Karagol (2005) investigates the causal relationship between defence expenditures and external debt. The results suggest both longhaul and short-term unidirectional causality running from defence expenditures to external debt, but not vice versa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In another study for the same sample and country, Karagol (2005) investigates the causal relationship between defence expenditures and external debt. The results suggest both longhaul and short-term unidirectional causality running from defence expenditures to external debt, but not vice versa.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research findings show that GDP per capita, the rate of export to GDP, social infrastructure, and education have a positive effect on external debts. Karagöl (2005) investigated the causal relationship between defence expenditures and external debt in Turkey over the period 1955-2000. The findings show that there is a causality from defence expenditures to external debt.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…By estimating long-run elasticity, he found that higher defense spending led to higher external debt, and increasing income contributed to repayment of foreign debts by Middle Eastern countries. Karagol (2005) studied the relationship between defense spending and foreign debt in Turkey from 1955 to 2000 through cointegration and a vector error correction model, finding a positive correlation between the two.…”
Section: Methodsmentioning
confidence: 99%
“…The literature observes that an increase in defense spending will squeeze out other government consumption and capital expenditures, affecting economic growth. Many scholars have explored this issue (Chester, 1978;Deger and Smith, 1983;Dunne and Vougas, 1999;Karagol, 2005). Although studies have explored the effect of interest on military spending (Calleo, 1981;Chowdhury, 1991;Fordham, 2003) no studies have examined the effect of interest on the arms race between the two countries using their interest rates as a control variable.…”
Section: Asian Economic and Financial Reviewmentioning
confidence: 99%